Risk factors associated with adenoma recurrence following cold snare endoscopic mucosal resection of polyps ≥ 20 mm: a retrospective chart review - Suresh, Suraj; Zhang, Jinyu; Ahmed, Abdelwahab; Abu Ghanimeh, Mouhanna; Elbanna, Ahmed; Kaur, Randeep; Isseh, Mahmoud; Watson, Andrew; Dang, Duyen T.; Chathadi, Krishnavel V.; Pompa, Robert; Singla, Sumit; Piraka, Cyrus; Zuchelli, Tobias (Endoscopy International Open, 2021)
Background and study aims Cold snare endoscopic mucosal resection (EMR) is being increasingly utilized for non-pedunculated polyps ≥ 20 mm due to adverse events associated with use of cautery. Larger studies evaluating adenoma recurrence rate (ARR) and risk factors for recurrence following cold snare EMR of large polyps are lacking. The aim of this study was to define ARR for polyps ≥ 20 mm removed by cold snare EMR and to identify risk factors for recurrence.Patients and methods A retrospective chart review of colon cold snare EMR procedures performed between January 2015 and July 2019 at a tertiary care medical center was performed. During this period, 310 non-pedunculated polyps ≥ 20 mm were excised using cold snare EMR with follow-up surveillance colonoscopy. Patient demographic data as well as polyp characteristics at the time of index and surveillance colonoscopy were collected and analyzed.Results A total of 108 of 310 polyps (34.8 %) demonstrated adenoma recurrence at follow-up colonoscopy. Patients with a higher ARR were older (P = 0.008), had endoscopic clips placed at index procedure (P = 0.017), and were more likely to be Asian and African American (P = 0.02). ARR was higher in larger polyps (P < 0.001), tubulovillous adenomas (P < 0.001), and polyps with high-grade dysplasia (P = 0.003).Conclusions Although cold snare EMR remains a feasible alternative to hot snare polypectomy for resection of non-pedunculated polyps ≥ 20 mm, endoscopists must also carefully consider factors associated with increased ARR when utilizing this technique.